Women of the Midan : The Untold Stories of Egypt's Revolutionaries - Hafez, Sherine (Book collections on Project MUSE., 2019)
Though the testimonies of Egyptian women who participated in the revolution, Women of the Midan foregrounds the role of the gendered body as an agent of collective action and transformation--a practice and process that challenges traditional notions of how women are represented in the Middle East